Analisis Pengaruh Kecepatan Aliran Udara Terhadap Penurunan Temperatur Efektif Pada Alat Simulasi Ventilasi Tambang Bawah Tanah - Dhoni Syaputra; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. In underground mines the ventilation system is very important in terms of meeting the air respiratory needs of workers, cleaning dirty air, toxic gases, concentrating dust, regulating heat and humidity in the mine. The problem that often occurs in underground mining, especially in Sawahlunto is the high temperature temperature on the workers' mining front, so that the safety and comfort of the workers is no longer in line with the rules set by the Kepmen 555K/MPE/1995.To meet the standards of effective air and temperature requirements at the mining front, the author tries to conduct an experiment with an underground mine ventilation simulation tool located at the FT .UNP mine laboratory, the experiment was carried out by flowing different air flow velocities using suction fan, blow fan 16